2020
DOI: 10.3389/fspor.2020.00059
|View full text |Cite
|
Sign up to set email alerts
|

The Trade-Off of Virtual Reality Training for Dart Throwing: A Facilitation of Perceptual-Motor Learning With a Detriment to Performance

Abstract: Advancements in virtual reality (VR) technology now allow for the creation of highly immersive virtual environments and for systems to be commercially available at an affordable price. Despite increased availability, this access does not ensure that VR is appropriate for training for all motor skills. Before the implementation of VR for training sport-related skills takes place, it must first be established whether VR utilization is appropriate. To this end, it is crucial to better understand the mechanisms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 67 publications
3
40
4
Order By: Relevance
“…Moreover, while skills learnt in VR have been found to improve performance when switching to a real-world setting, the performance following training in VR is poorer compared with the performance when someone has trained in a real-world setting from the outset [ 57 ]. Additionally, studies suggest that improvements in skill that are made within the VR environment do not always generalise to real-world settings [ 58 ]. In fact, a recent study demonstrated that playing a generic dart game available on an HTC Vive headset resulted in a worsening of performance compared with real-world training [ 58 ].…”
Section: Efficacy Of Xr Use In Sportmentioning
confidence: 99%
“…Moreover, while skills learnt in VR have been found to improve performance when switching to a real-world setting, the performance following training in VR is poorer compared with the performance when someone has trained in a real-world setting from the outset [ 57 ]. Additionally, studies suggest that improvements in skill that are made within the VR environment do not always generalise to real-world settings [ 58 ]. In fact, a recent study demonstrated that playing a generic dart game available on an HTC Vive headset resulted in a worsening of performance compared with real-world training [ 58 ].…”
Section: Efficacy Of Xr Use In Sportmentioning
confidence: 99%
“…Earlier studies have shown that training in a VR environment can be even better than training in real life, though there is also a risk of becoming over-dependent on the VR feedback [ 21 ]. Overall, the literature does not provide a clear answer as to whether performance improvements in VR successfully translates to better performance in real life [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some studies suggest that improvements in a VR context does not always generalize to real-life settings. For example, one recent study showed that playing a dart game available on HTC Vive resulted in worsening of real-life performance compared to real-life training; indeed, the dart throws actually got less accurate than dart throws prior to training in VR [ 17 ]. In other words, when it comes to the efficacy of improving motor skills through training in VR, results have been mixed.…”
Section: Introductionmentioning
confidence: 99%
“…The unique practice conditions of non-immersive VEs may impact movement execution and performance variability. For example, interactions with virtual objects involve differing perceptual-motor affordances as compared to interaction with objects in the physical environment ( 55 , 56 ). A lack of 3D depth cues in a non-immersive VE influences distance estimates of where objects are in space, which may increase uncertainty about movement accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of 3D depth cues in a non-immersive VE influences distance estimates of where objects are in space, which may increase uncertainty about movement accuracy. In addition, hand-held peripheral controllers that track movement (such as the one required by the Nintendo Wii or the HTC VIVE) may influence task interaction ( 56 ) as opposed to direct motion tracking.…”
Section: Introductionmentioning
confidence: 99%